STUDENT'S ATTITUDE TOWARDS SUBJECT CHEMISTRY - RESEARCH USING TEST OF INDEPENDENCE - Vladislav, BIBA; KLEPANCOVÁ, Michaela (Trends in education, 2015)
The paper describes the results of research among students at Institute of Technology and Business in Czech Budejovice, whose relationship to chemistry was investigated by a questionnaire. We focused on connections between responses using statistical test of independence.
Keywords: chemistry; questionnaire research; independence test.